2021
DOI: 10.1186/s12913-021-07224-3
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging e-Learning technology to enhance pre-service training for healthcare trainees in Ghana: evidence from a pilot project and pointers to policy reforms

Abstract: Background E-Learning solutions are increasingly being advocated to augment existing traditional teaching and learning efforts in health training institutions. Unfortunately, these emerging technologies rarely focus on health sciences education within the context of public universities, hence the need for this study. This project evaluated experiences of healthcare trainees with a pilot e-Learning project (SMART e-Learning project) initiated in one of Ghana’s public universities in 2017. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 22 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…[14] An article discussing the use of devices to access the e-learning facility highlighted that the most reliable were computer lab desktops, personal mobile phones, personal laptops, and personal tablets. [15] However, it was found that the most common means used by students to access the internet was their smartphone or tablet. [14,[16][17][18] It also appears that half the students belonged to average households.…”
Section: Results Of Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…[14] An article discussing the use of devices to access the e-learning facility highlighted that the most reliable were computer lab desktops, personal mobile phones, personal laptops, and personal tablets. [15] However, it was found that the most common means used by students to access the internet was their smartphone or tablet. [14,[16][17][18] It also appears that half the students belonged to average households.…”
Section: Results Of Synthesismentioning
confidence: 99%
“…[14] Published by Sciedu Press In a university with a computer laboratory, some respondents used computers belonging to the school to access the Internet (63%). [15] In some studies, there was no structure dedicated to digital innovation tools, [15] and in many regions, the Internet was not widely available or accessible. [10] Mbah, whose study focused on nursing educators, found that teachers had laptops.…”
Section: Results Of Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the use of ICT, its advantages seem to be undermined by delimiting factors. From the management perspective, Alhassan et al (2021) and Larbi-Apau (2011), reported on inadequate funds to carry out the needed ICT infrastructure expansions, inadequate human resources, and inadequate lecturers with the requisite capacity, knowledge and skills to integrate technology into teaching. Equally challenging is students' low pedagogical use of ICT and low pre-university enrolment knowledge in computer literacy (Adarkwah, 2021;Buabeng-Andoh & Issifu, 2015).…”
Section: The Role Of Ict In Higher Education In Ghanamentioning
confidence: 99%